Strictly Decreasing Solutions of a Class of Iterative Equations on the Unit Circle - Wei Song; Sheng Chen; Xunbo Yin (Discrete Dynamics in Nature and Society)
We discuss the strictly decreasing solutions of a class of iterative equations on the unit circle T1. The conditions for the existence, uniqueness, and stability of such solutions are presented.